ENHANCING PRODUCTIVITY VIA STRENGTHENING ACHIEVEMENT MOTIVATION AND EFFECTIVE OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT - Erna Herlina; Anoesyirwan Moeins; Widodo Sunaryo (CV. Four Son Scholarship, 2024)
This study investigates the effects of occupational safety and health management and achievement motivation on employee productivity at PT. XYZ (Persero). Utilizing a mixed-method approach, the research integrates quantitative surveys with qualitative analyses. Data were gathered from the Transmission Implementation Units (UPT) in Bogor and Karawang, covering the years 2017 to 2021. Findings reveal that both effective occupational safety and health management and strong achievement motivation significantly and positively impact employee productivity. While both factors directly improve productivity, the mediating role of achievement motivation is less effective compared to the direct influence of occupational safety and health management. The study concludes that enhancing the effectiveness of occupational safety and health management alongside boosting achievement motivation can markedly increase employee productivity at PT. XYZ (Persero). The company is advised to improve occupational safety and health training, closely monitor the work environment, and implement reward programs to recognize and incentivize high-performing employees